EpCam is required for maintaining the integrity of the biliary epithelium. (22nd June 2021) - Zhan, Yougen; Ward, Stephen C.; Fiel, Maria Isabel; Teruya‐Feldstein, Julie; McKay, Eileen M.; Dekio, Fumiko
Abstract: Background & Aims: Tufting enteropathy (TE) is a rare congenital disorder often caused by mutations in the gene encoding epithelial cell adhesion molecule (EpCam). The disease leads to diarrhoea, intestinal failure and dependence on total parenteral nutrition (TPN). These patients often have liver impairments, but the pathology and mechanism of the damage are not well understood. We evaluated liver biopsies from TE patients to understand the pathophysiology. Methods: We identified three patients with TE who underwent liver biopsy. Two normal controls and 45 patients on TPN secondary to short gut syndrome were selected for comparison (five were age‐ and TPN duration matched to the TE patients). Results: We found that all TE patients showed a complete loss of EpCam expression in enterocytes and biliary epithelial cells, while the normal and TPN groups show basolateral expression. Histologically TE patients showed ductopenia, which was not seen in control groups. E‐cadherin and β‐catenin are normally located along the lateral membrane of biliary epithelial cells. However, they were relocated to the apical membrane in TE patients, indicating a defect in the apical‐basal polarity of cholangiocytes. We examined hepatic reparative cells and found near absence of hepatic progenitor cells and intermediate hepatobiliary cells with mild reactive ductular cells in TE patients. Conclusion: Our findings show that TE is associated with disrupted polarity of cholangiocyte and ductopenia. We demonstrate for the first time a role of EpCam in the maintenance of integrity of biliary epithelium. We also provided evidence for a disrupted development of hepatic reparative cells.